Profile and development of adaptive behavior in adults with autism spectrum disorder and severe intellectual disability - Adrien, Jean-Louis; Blanc, Romuald; Thiébaut, Eric (Frontiers in Psychiatry, 2025)
BackgroundThis study examined the profiles of adaptive behavior development in adults with autism spectrum disorder (ASD) and severe intellectual disability (ID), and the relationships between the levels of the different domains and subdomains of adaptive development and the intensity of autistic symptomatology.ParticipantsThis study involved 71 adults (44 men and 27 women with average ages of 39 years 7 months and 36 years 2 months, respectively) living in medico-social institutions and having a level of adaptive development corresponding to age below 3 years 4 months and a level of cognitive development corresponding to ages between 12 and 24 months.MethodsASD was diagnosed using Pervasive Development Disorder-Mental Retardation Scale (PDD-MRS) and Childhood Autistic Rating Scale (CARS), ID and its severity were determined based on the Diagnostic Statistical Manual-5 (DSM-5) criteria, and the very low cognitive developmental level was assessed using the Socio-emotional Cognitive Evaluation Battery (Adrien, Pearson-ECPA, 2007), adapted for adults (SCEB-A). Adaptive development was assessed using the Vineland-II tool.ResultsThe adaptive developmental profile was heterogeneous: the median levels of the three domains of socio-adaptive development differed significantly from each other, and the domain of Daily Living was the most developed. Among the nine subdomains, the weakest developmental levels corresponded to Expressive Language, Interpersonal Relationships, and Play/Leisure. By contrast, the highest levels corresponded to Personal and Domestic Autonomy. Significant and negative relationships were noted between the intensity of autism severity and the levels of development in Communication and Daily Living but not Socialization. These results are discussed to highlight the best-developed adaptive domains and those to be improved.